Sustainable strategy of health and safety assessment in high rise commercial buildings - Yahya, Mohamad Ridzuan; Ibrahim, Md. Najib (Ontario International Development Agency, 2012)
In Malaysia scenario, various obstacles have to be faced by the building maintenance teams controlling all activities related to the high rise office building and its system. The crucial issue is to face serious problems with health and safety aspect of the building. This study aims to evaluate the health and safety performance of high rise office buildings, using a basic assessment method. An assessment method based on a hierarchy of building performance indicators concerning the quality of design factor and management factor with five attributes such as architectural design, building services design, the surrounding environment, operation and maintenance, and facilities management. Eleven high rise office buildings were randomly selected in Klang Valley, Malaysia and assessed through site inspections, desk searches, and interviewed facilities management personnel (FM), outsourced contractors/consultants (OS), building owners (BO) as well as (T) tenants. A performance analysis was conducted to examine and compare the overall health and safety performance of the buildings. The results had shown that there were significant variations in health and safety conditions across buildings, although they are situated within a single locality. After describing the current situation and problems, this paper concludes that most of the variations in building health and safety conditions were attributed to differences in building management systems rather than building designs. It is envisaged that further research can be conducted to investigate the relationship between building performance and extraneous factors, such as building age, management structure, and scale of development.